INVESTASI CINA MELALUI BELT AND ROAD INIATIVE (BRI) DAN PENGARUHNYA TERHADAP EKONOMI INDONESIA - Muhammad Reyhan Alamsyah; Ahmadn Jamaa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Belt and Road Initiative (BRI) is an ambitious initiative by the Chinese government aimed at enhancing infrastructure and trade connectivity with 68 countries worldwide. In the context of Indonesia, China has made significant investments in various sectors, including transportation, energy, telecommunications, tourism, and other strategic sectors. In this research, the researchers used secondary data to demonstrate that Chinese investment through the BRI has had a significant positive impact on Indonesia's economy. One of the main impacts is the improvement of infrastructure connectivity. BRI projects have strengthened Indonesia's transportation network by constructing ports, toll roads, and railways that connect different regions. This has increased efficiency in the distribution of goods and strengthened domestic market integration. Additionally, Chinese investment has also led to increased Foreign Direct Investment (FDI) in Indonesia. Many Chinese companies participating in BRI projects have opened new investments in Indonesia, creating job opportunities and bringing new technologies and expertise to Indonesia's economy. However, there are several challenges that need to be addressed. Environmental risks arise from large-scale infrastructure projects, and the trade imbalance with China is a concern. The Indonesian government needs to ensure that these investments contribute to sustainable development and benefit the Indonesian society as a whole. Keywords: China, Investment, BRI, Connectivity